MENINGKATKAN HASIL BELAJAR MATERI POLIMER MELALUI PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER PADA SISWA KELAS XII IPA SMAN 2 PONTIANAK - Danggus, Grardus (Jurnal Pendidikan Matematika dan IPA, 2014)
This research has been conducted to recognize the improvement of the students study achievement in polymer lesson at 12th grade of science program in SMAN 2 Pontianak by the application of cooperative learning model type numbered heads together. The form of this research is Classroom Action Research. The research was conducted in three cycles. The students learn about the meaning and the reaction how the polymer is formed, the classification of polymer, kinds of plastic, the use and the impact of polymer as well. The instruments used are the students’ test achievement and questioners. Result of this research on the first cycle the percentage of the study completeness is 70,97%, the second cycle is 75% and the third cycle is 84,38%. It can be concluded that there is improvement on the students study result. It is recommended for the teachers to choose cooperative learning model type numbered heads together become one of the learning model alternative in polymer lesson to improve of the students’ study result. Keywords: Numbered heads together, polymer.